2007
DOI: 10.1016/s0079-6123(07)66006-3
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of spontaneous activity for the coding of the tinnitus sensation

Abstract: In this chapter we will present support for the hypothesis that synchronous neuronal activity of cell assemblies within the auditory cortex could be the underlying neural code of tinnitus. Such synchronous activity is reflected in the ongoing oscillatory activation pattern that can be recorded non-invasively using MEG and EEG techniques. We conclude that such an oscillatory model of tinnitus can explain many different observations regarding tinnitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
133
4
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(156 citation statements)
references
References 42 publications
(51 reference statements)
14
133
4
5
Order By: Relevance
“…However, Ashton et al found no consistent relationship between the laterality of TI and the side of maximal gamma activity (ipsilateral in five patients and contralateral in three). This finding contradicts the claim by Weisz et al (2007b) that the scalp distribution of gamma activity determines TI laterality. Also in contrast to previous MEG studies, Ashton et al found no evidence of abnormal activity in any of the low-frequency bands.…”
Section: Human Neuroimaging Studiescontrasting
confidence: 89%
See 1 more Smart Citation
“…However, Ashton et al found no consistent relationship between the laterality of TI and the side of maximal gamma activity (ipsilateral in five patients and contralateral in three). This finding contradicts the claim by Weisz et al (2007b) that the scalp distribution of gamma activity determines TI laterality. Also in contrast to previous MEG studies, Ashton et al found no evidence of abnormal activity in any of the low-frequency bands.…”
Section: Human Neuroimaging Studiescontrasting
confidence: 89%
“…It is interesting to note that no abnormalities were reported in the gamma frequency band because "downsampling of the data did not permit analysis in this frequency band". Gamma band activity was examined in a subsequent study in which data were acquired at the same sampling rate (678 Hz) and filtered using the same bandwidth (1 to 200 Hz), but were not downsampled (Weisz et al, 2007b). 26 TI patients were compared with 21 controls.…”
Section: Human Neuroimaging Studiesmentioning
confidence: 99%
“…Moreover, electroencephalography studies have demonstrated that γ-band activity in the auditory cortex reflects the tinnitus intensity (29), analogous to intensity coding in normal auditory perception (30). The γ-band activity noted in tinnitus patients goes along with decreased α (31) and increased θ activity (27,32). This coupled θ-γ activity coordinates activity in distributed cortical areas, providing a mechanism for effective communication between these distributed areas (33).…”
mentioning
confidence: 98%
“…As individuals with tinnitus continuously hear an internal sound, it is conceivable that the power of their tau rhythms is reduced. Weisz et al 2007 (Chapter 6) provide more information regarding the relationship between ongoing oscillatory activity and tinnitus.…”
mentioning
confidence: 99%